Nilai Tukar Rupiah Riil Equilibrium Sebelum dan Selama Masa Krisis - Awaluddin, Imam (Jurnal Ekonomi dan Pembangunan Indonesia, 2004)
This study concerns about how much economic factors have impact on real exchange rate equilibrium and how much exchange rate misalignment occurs. The objective is to find the level of rzal exchange rate equilibrium before and during the crisis. Real exchange rate equilibrium is founded from Behavioral Equilibrium Exchange Rate approach. From regression estimation we will find real exchange rate equilibrium, which will be compared with actual real exchange rate. The result is real exchange rate misalignment or deviation of real exchange rate from its equilibrium level.